Elite sport is not an additional source of distress for adolescents with high stress levels - Gerber, M.; Holsboer-Trachsler, E.; Pühse, U.; Brand, S. (Perceptual and Motor Skills, 2011)
This study examined whether participation in elite sport interacts with stress in decreasing or increasing symptoms of depression and anxiety among adolescents, and further, whether the interplay between participation in high-performance sport and stress is related to the perceived quality of sleep. 434 adolescents (278 girls, 156 boys; age: M = 17.2 yr.) from 15 "Swiss Olympic Sport Classes" and 9 conventional classes answered a questionnaire and completed a 7-day sleep log. Analyses of covariance showed that heightened stress was related to more depressive symptoms and higher scores for trait-anxiety. Moreover, those classified as having poor sleep by a median split cutoff reported higher levels of depressive symptoms. No significant (multivariate) main effects were found for high-performance sport athletes. Similarly, no significant two- or three-way interaction effects were found. These results caution against exaggerated expectations concerning sport participation as a stress buffer. Nevertheless, participation in high-performance sport was not found to be an additional source of distress for adolescents who reported high stress levels despite prior research that has pointed toward such a relationship.